INDEX GLOBE VOL 24 NO 2 Tahun 2022: (Classification of Shallow Water Benthic Habitat in Barrang Caddi Island with OBIA Approach using Sentinel-2 and SPOT-7 Satellite Images with Bayesian and K-Nearest Neighbor Algorithm) - Sekretariat Redaksi Majalah Ilmiah Globe (Majalah Ilmiah Globe, 2022)
MIG